Pogostost poškodb z ostrim predmetom v operacijskem bloku Kliničnega centra Ljubljana - Stare, Mateja (Obzornik zdravstvene nege, 2003)
The article presents the frequency of injuries with sharp objects among healthcare workers in the operating theatre in the Clinical Center in Ljubljana. In the first part of the article, causes and possibilities for suchincidents are presented. Health workers are exposed to infection in contact with an infectious patient, his body fluids, secretions and excrements. Risk depends on the intensity and frequency of contacts, which areagain dependent on the nature of work and preventive measures, proneness ofa health worker to infection etc. The second part of the article describes and explains the research on incidents during the last two months in 2001. Research was carried out on 120 operating theatre nurses, anaesthesia nurses and nursing aides working in the operating theater of the Clinical Center in Ljubljana. The results of the research work show the awareness of health workers of the possibilities of injuries with sharp objects and of the fact that incident happen all the time and are not properly dealt with.
Keywords: Bolezen, prenos, bolnik-na- strokovnjaka; Cross Infection; Disease Transmission, Patient-To-Professional; Handwashing; Igla, vbodnine; Infekcija navzkrižna; infekcije; Needlestick Injuries; Oboperativna nega; Operacijske sobe; Operating Rooms; Perioperative Nursing; poškodbe; Prevention And Control; Roka, umivanje; vzroki; zdravstveni delavci